Willie & me : a baseball card adventure - Gutman, Dan (Gutman, Dan. Baseball card adventures., 2015)
"Joe "Stosh" Stoshack uses his power to time travel using baseball cards to go back to 1951, when Bobby Thomson hit the famous Shot Heard Round the World home run to win the National League pennant for the New York Giants"--